Optimalisasi Micro Influencer dalam Aktivitas Periklanan di Tiktok (Bigbang Agency) - Risang Abdhi Sanjaya; Mustiawan Mustiawan; Yulia Rahmawati (PERSPEKTIF, 2025)
This study explores the optimization of micro influencer utilization in digital advertising campaigns conducted by BIGBANG Agency on the TikTok platform. The main issue addressed is the selection process of micro influencers to ensure maximum impact on clients' advertising efforts, emphasizing the importance of trustworthiness, expertise, and attractiveness. Employing a qualitative approach and a case study method, data were collected through in-depth interviews, observations, and documentation involving the agency and selected micro influencers. The source credibility theory serves as the primary analytical framework. The findings reveal that BIGBANG Agency selects micro influencers based on honesty, audience engagement levels, content quality, and the alignment of appearance and communication style with the product’s character. The agency also allows creative freedom, enabling influencers to produce authentic yet campaign-aligned content. Open, flexible, and collaborative communication strategies are key to creating genuine and relevant content, which enhances audience trust and promotes campaign effectiveness. The study's limitation lies in its single-object focus and descriptive nature without quantitative effectiveness measurement. Future research should include multiple agencies for a more comprehensive comparison and adopt a quantitative approach to evaluate campaign performance more accurately.